Fatigue performance of flexible steel fibre reinforced rubberised concrete pavements. (15th August 2019) - Alsaif, Abdulaziz; Garcia, Reyes; Figueiredo, Fabio P.; Neocleous, Kyriacos; Christofe, Andreas; Guadagnini, Maurizio; Pilakoutas, Kypros
Highlights: Flexible SFRRuC can be constructed using waste tyre materials. Mechanical and fatigue performance of SFRRuC are presented. Three probabilistic models are used to derive the ( Pf -S-N ) relationships. SFRRuC pavements can accommodate large subgrade settlements. Abstract: Recycled rubber particles and steel fibres from end-of-life tyres have the potential to enhance the flexibility and ductility of concrete pavements and produce more sustainable pavement solutions. However, the fatigue behaviour of such pavements is not fully understood. This article investigates the mechanical and fatigue performance of steel fibre reinforced concrete (SFRC) and steel fibre reinforced rubberised concrete (SFRRuC). Specimens tested were cast using rubber particles as replacement of natural aggregates (0%, 30% and 60% by volume), and using a blend of manufactured and recycled tyre steel fibres (40 kg/m 3 ). Prisms were subjected to four-point flexural cyclic load (f = 15 Hz) at stress ratios of 0.5, 0.7, 0.8 and 0.9. The results show that, compared to plain concrete, the addition of steel fibres alone improves the fatigue stress resistance of concrete by 11% (at 25% probability of failure). The replacement of natural aggregates with rubber particles improves the flexibility of SFRRuC (from 51 GPa elastic modules for plain concrete to 13 GPa for SFRRuC), but reduces its fatigue stress resistance by 42% (at 25% probability of failure). However, a probabilistic analysis of the fatigue life data and overall design considerations show that the flexible SFRRuC can be used for pavements. To account for the effect of fatigue load, the Concrete Society approach included in TR34 is modified to account for SFRRuC pavements. Finite element analyses show that flexible SFRRuC pavements can accommodate large subgrade movements and settlements and result in much smaller cracks (up to 24 times) compared to SFRC pavements.